ANALISIS EPIC MODEL TERHADAP EFEKTIVITAS IKLAN ONLINE SEBAGAI MEDIA PROMOSI DI YOUTUBE TERHADAP KEPUTUSAN PEMBELIAN POCARI SWEAT - Ade Nurhayati; Meki Munawar; Isna Biduri Urfa (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the Effect of Online Advertising Effectiveness as a Promotional Media for Pocari Sweat on YouTube on Purchase Decisions. The research method used is quantitative with an associative approach. Sampling was done through purposive sampling technique by distributing questionnaires to 97 respondents who are YouTube users in the Purwakarta Regency area. The data analysis method used is validity test, reliability test, classical assumption test, multiple linear regression test, and hypothesis testing. The data was processed with the help of the IBM SPSS version 25 program. This study used the EPIC Model as a method of calculating the effectiveness and Multiple Linear Regression as a method to determine the effect of the EPIC dimension on purchasing decisions. The results of this study prove that Pocari Sweat advertising is considered effective with a value of 4.12, and also the EPIC dimension influences purchasing decisions either partially or simultaneously. The dimension of EPIC affects purchasing decisions by 40.8%, while the remaining 59.2% is influenced by variables outside the research variables.